Change in Some Chemical Parameters of two Environment Polluting Waste (Fertilizer Factory Effluent and Sweetmeat Factory Waste) Media After Culture of Three Important Microalgae (Bangladesh Journal of Scientific and Industrial Research, 2008)
Some chemical parameters of fertilizer factory effluent (FFE) and sweetmeat factory waste (SFW) were analyzed before and after culture of three important microalgae (Spirulina platensis, Chlorella ellipsoidea and Scenedesmus obliquus) to make the waste environment friendly and to develop their economic use. Among the two wastes significantly (P